2021
DOI: 10.1007/s11263-021-01437-z
|View full text |Cite
|
Sign up to set email alerts
|

An Exploration of Embodied Visual Exploration

Abstract: Embodied computer vision considers perception for robots in novel, unstructured environments. Of particular importance is the embodied visual exploration problem: how might a robot equipped with a camera scope out a new environment? Despite the progress thus far, many basic questions pertinent to this problem remain unanswered: (i) What does it mean for an agent to explore its environment well? (ii) Which methods work well, and under which assumptions and environmental settings? (iii) Where do current approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
32
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(33 citation statements)
references
References 59 publications
(162 reference statements)
0
32
0
1
Order By: Relevance
“…These methods have been largely used and improved [24], [25], [17] or combined in a hierarchical exploration algorithm [16], [2]. However, when applied with noisy odometry and localization sensors or in highly complex environments, geometric approaches tend to fail [8], [17], [18]. In light of this, increasing research effort has been dedicated to the development of learning-based approaches, which usually exploit DLR to learn robust and efficient exploration policies.…”
Section: A Geometric Robot Exploration Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…These methods have been largely used and improved [24], [25], [17] or combined in a hierarchical exploration algorithm [16], [2]. However, when applied with noisy odometry and localization sensors or in highly complex environments, geometric approaches tend to fail [8], [17], [18]. In light of this, increasing research effort has been dedicated to the development of learning-based approaches, which usually exploit DLR to learn robust and efficient exploration policies.…”
Section: A Geometric Robot Exploration Methodsmentioning
confidence: 99%
“…In the context of robotic exploration and navigation tasks, the introduction of photorealistic simulators has represented a breeding ground for the development of self-supervised DRLbased visual exploration methods. Ramakrishnan et al [18] identified four paradigms for visual exploration: novelty-based, curiosity-based (as defined above), reconstruction-based, and coverage-based. Each paradigm is characterized by a different reward function used as a self-supervision signal for optimizing the exploration policy.…”
Section: Learning-based Robot Exploration Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several papers contribute novel metrics and taxonomies for the evaluation of different tasks, including multi-object tracking (Luiten et al 2021), semantic segmentation (Yan et al 2021), visual place recognition (Zaffar et al 2021), image quality assessment (Ding et al 2021), conditional image generation (Benny et al 2021), and embodied exploration (Ramakrishnan et al 2021).…”
mentioning
confidence: 99%